Analisis Penerapan Aplikasi Sistem Informasi Aparatur Sipil Negara (SIASN) di Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kabupaten Ogan Komering Ulu - Ramadhanty, Maillyvia; Sari, Yunita; Efrianti, Rini; Purnowati, Indah (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
The purpose of this analysis is to assess the implementation of the State Civil Apparatus Information System (SCAIS) as well as identify areas that need to be improved in the system to improve its function at the Personnel and Human Resources Development Agency (PHRDA) of Ogan Komering Ulu (OKU) Regency. This research uses a descriptive approach with qualitative data collection. The results of this research conclude that 1) the implementation of the State Civil Apparatus Information System (SCAIS) in Ogan Komering Ulu Regency has been carried out effectively and efficiently, but it still needs to be improved periodically and it is not easy to become complacent in order to realize e-governance; and 2) optimizing the State Civil Apparatus Information System (SCAIS) managed by PHRDA Ogan Komering Ulu (OKU) Regency by maximally inputting data on state civil apparatus employees within the OKU Regency government and socializing it to the Regional Apparatus Organizations (RPO) in OKU so that realizing up-to-date and integrated personnel data.